Product distribution of the thermal and catalytic fast pyrolysis of karanja (Pongamia pinnata) fruit hulls over a reusable silica-alumina catalyst. (1st June 2019) - Tan, Y.L.; Abdullah, A.Z.; Hameed, B.H.
Abstract: The conversion of karanja fruit hulls by fast pyrolysis was investigated using a drop-type two-stage reactor. The ex-situ catalytic fast pyrolysis of karanja fruit hulls over a silica-alumina catalyst was performed at 500 °C and at a catalyst loading of 0.1 g. The obtained bio-oil yield was 41.09 wt%. The bio-oil contained 84.38% carbonyls. The silica-alumina catalyst reduced the liquid yield to 39.73 wt%. The production of aromatics and hydrocarbons in bio-oil was enhanced, whereas the yield of carbonyls was reduced from 84.38% (non-catalytic) to 7.83% (catalytic). After catalyst regeneration, the aromatic yield was increased from 30.08% (1st run) to 52.18% (5th run), and the deoxygenation degree was increased from 35.15% (1st run) to 57.13% (5th run), thereby demonstrating that the silica-alumina catalyst had satisfactory reusability. The amount of catalytic coke was reduced after catalyst regeneration, because less hard coke was formed.